Contemporary treatment options for male hypogonadism - Paweł Sojka; Joanna Popiołek; Jakub Szczerba; Szymon Pokora; Agata Stefanowicz; Dominika Pokładnik; Katarzyna Jeleń; Karolina Pokora; Adam Podsiedlik; Alicja Poloczek (Kazimierz Wielki University, 2023)
Introduction Male hypogonadism is a disease in which testicular function is impaired. Its symptoms are due to testosterone deficiency and most of them show low specificity. These include reduced libido, erectile dysfunction and mood disorders, among others. The biochemical indicator of hypogonadism is a testosterone concentration below 350 ng/ml (12nmol/L), according to the European Association of Urology (EAU). The increased incidence of hypogonadism is associated with aging and the presence of comorbidities such as type II diabetes and obesity. Men with testosterone deficiency have an increased risk of cardiovascular disease and premature death. Goals Summary of current reports on the diagnosis and treatment of hypogonadism. An overview of the advantages and disadvantages of the different types of formulations used in testosterone replacement therapy. Methods Review of literature available in PubMed and Google Scholar databases. Conclusions The medical interview, physical examination and ancillary tests help to classify hypogonadism appropriately. Measuring the concentration of gonadotropins, helps diversify primary from secondary hypogonadism. Testosterone replacement therapy (TRT) uses formulations that have varying release profiles, route of administration and drug formulation. The choice of testosterone product should involve age, lifestyle, and individual preferences of the patient.